Analysis of the Effect of Institutional Ownership Profitability, Sales Growth and Leverage on Tax Avoidance in Construction Subsector Companies - Ramadan Harahap (Budapest International Research and Critics University, 2021)
This study Purpose to analyze the Effect of Institutional Ownership, Profitability, Sales Growth and Leverage on Tax Avoidance in Construction Subsector Companies listed on the Indonesia Stock Exchange in 2017 – 2019, this study amounted to 16 Construction Subsector companies listed on the Indonesia Stock Exchange. by using the type of associative analysis research with panel data design that is a combination of time series data and cross-sectional data. The type of data used is panel data (pooled data), panel data regression analysis with Fixed Effect Model (FEM) estimation method and reviews 9 SV program. Hypothesis testing carried out is the Coefficient of Determination Test (R Square), F-Test, and t-Test. The results showed that the institutional ownership variable had a negative and positive effect on tax avoidance, the Profitability variable had a positive and positive effect on tax avoidance. The sales growth variable had a positive and positive effect on tax avoidance. Leverage has a negative and positive effect on tax avoidance.